Effectiveness of Vision Therapy for Divergence Insufficiency: A Case Series. - Chhetri, Santosh; Belbase, Umesh; Cantó-Cerdán, Mario; Shah, Aashish Kant (Optometry & Visual Performance, 2025)
Background: When base-out prism glasses are not successful in maintaining binocularity and eliminating symptoms in divergence insufficiency, vision therapy serves as a viable non-surgical treatment option. We report three cases of patients with divergence insufficiency who improved negative fusional vergence, eliminated symptoms, maintained binocularity, and achieved stereopsis through vision therapy. Case one: An 18-year-old female student presented with complaints of an occipital headache and occasional double vision, which was more pronounced at a distance and in the evening for the past four years. Orthoptic evaluation led to a diagnosis of divergence insufficiency. She was treated with base-out prism glasses and vision therapy. Over five months, the prism glasses were gradually weaned off, and the patient became asymptomatic with well-controlled deviation. Case two: A 35-year-old male driver had to leave his job due to double vision. He had been using prism glasses for the past ten years. However, his negative fusional vergence and prism glasses were insufficient to control the deviation. After several sessions of vision therapy, his double vision was eliminated, and he was able to resume driving. Case 3: A 12-year-old female student had headaches, usually while focusing on the board at school. She was diagnosed with left eye suppression and divergence insufficiency. After several sessions of office and home-based vision therapy, she experienced relief from symptoms and achieved binocularity and stereopsis. Conclusion: Vision therapy is a non-surgical treatment approach for divergence insufficiency and offers an effective and promising alternative to surgical intervention. These three cases highlight successful and positive outcomes in patients with divergence insufficiency.